The efficacy of controlled antibiotic release for prevention of polyethyleneterephthalate- (Dacron-) related infection in cardiovascular surgery - Karck, Matthias; Forgione, L.; Haverich, Axel (Clinical materials, 1993)
Infection of prostheses containing polyethyleneterephthalate (Dacron) remains a dreaded complication in cardiovascular surgery despite perioperative antibiotic (AB) prophylaxis. Dacron, which is widely applied as a fabric for manufacturing vascular prostheses and also the sewing rings of artificial heart valves, remains a source for infection once implanted in the body. In order to increase the AB concentration in Dacron, an experimental study including topical application of the gentamicin derivative EMD 46/217 and fibrin sealant (F) as AB carrier was initiated. In-vitro pretreatment of Dacron with the gentamicin derivative and F was followed by constant AB release for three weeks. In a subsequent animal study, four Dacron rings with different pretreatments were implanted in the descending aorta of ten pigs after direct contamination with 108 Staph. aureus solution. One ring was pretreated with the AB/F compound, a second ring with the AB alone. Ring 3 (no pretreatment) and ring 4 (F alone) served as controls. After one week, the Dacron rings and their corresponding implantation sites were asserved for measurement of AB content and for culture. The AB content of AB/F rings was 24·99 ± 7·16 μg/g wet weight, while Dacron rings pretreated with the AB alone contained no measurable drug amounts, with the exception of one specimen (0.5 μg/g) (AB/F versus AB rings: P < 0·0005 The corresponding implantation sites to AB/F rings contained 1·07 ± 0·54 μg/g AB, whereas in only 2/10 implantation sites of AB rings were low AB levels found 0·05 and 02 μg/g (AB/F versus AB ring implantation sites: P < 0·0005 While all Dacron rings, which served as controls and 9/10 Dacron rings pretreated with antibiotic alone were infected, 5/10 AB/F rings remained sterile after culture (AB/F versus AB rings: P = 0·05). This finding correlated with the AB content in the Dacron rings. Therefore, pretreatment of Dacron with the AB/F compound results in bounding of sufficient amounts of AB for at least one week. This measure for controlled release ou antibiotics can serve as a prophylactic tool against perioperative infection related to implantation of Dacron in cardiovascular surgery.
Gesehen am 12.01.2022